Use of programmable devices and language VHDL in the teaching of digital control - Noga, K. M. (Scientific Journal of Gdynia Maritime University, 2017)
The article presents some examples of laboratory exercises of programmable logic devices and VHDL language which are used in teaching digital technique on Electrical Engineering Faculty in Gdynia Maritime University.